(untitled) (Ameghiniana, 2015)
The early evolution of Ornithodira –the clade including pterosaurs and dinosaurs– is poorly known. Until a decade ago, the basal radiation of Dinosauromorpha, the clade including dinosaurs and birds, was poorly understood because of the poor fossil record restricted to specimens known from the Ladinian Chañares Formation in Argentina. Over the last years the discovery of several non-dinosaurian dinosauromorphs dramatically expanded this record and also demonstrated that this group –previously restricted to de Middle Triassic– survived at least well into the Norian. Although Norian non-dinosaurian dinosauromorphs have been reported from several regions around the world, the only known Norian non-dinosauriform dinosauromorphs –Dromomeron romeri Irmis, Nesbitt, Padian, Smith, Turner, Woody, and Downs and Dromomeron gregorii Nesbitt, Irmis, Parker, Smith, Turner, and Rowe– come from North America. We report here the first record from the Southern Hemisphere of a non-dinosauriform dinosauromorph, Dromomeron gigas sp. nov., from the Norian Quebrada del Barro Formation, northwestern Argentina. A phylogenetic analysis recovers Dromomeron gigas nested into the monophyletic group Lagerpetidae, and as the sister taxon to Dromomeron romeri. The inclusion of D. gigas within Lagerpetidae suggests that body size increased in this lineage over time, as was previously demonstrated for Dinosauriformes as a whole, and that lagerpetids reached a larger size than previously thought. Finally, the new finding provides new information on the basal radiation of Dinosauromorpha constituting the first record of a Norian association of dinosaurs with non-dinosauriform dinosauromorphs outside North America. Resumen. UN DINOSAUROMORPHA LAGERPETIDO NORIANO DE LA FORMACIÓN QUEBRADA DEL BARRO, NOROESTE DE ARGENTINA. La evolución temprana de Ornithodira, el clado que incluye pterosaurios y dinosaurios, es escasamente conocido. Hasta hace una década atrás, el conocimiento de la radiación basal de Dinosauromorpha, clado al que pertenecen dinosaurios y aves, estaba limitado a los especímenes provenientes del Ladiniano de la Formación Chañares de Argentina. En los últimos años, el descubrimiento de varios nuevos especímenes de dinosauromorfos no-dinosaurios expandió notablemente este registro demostrando que este grupo –previamente restringido al Triásico Medio– persistió bien avanzado el Noriano. Aunque los dinosauriformes no-dinosaurios provienen de diversos sitios de alrededor del mundo, los únicos registros de dinosauromorfos no-dinosauriformes norianos –Dromomeron romeri Irmis, Nesbitt, Padian, Smith, Turner, Woody, and Downs y Dromomeron gregorii Nesbitt, Irmis, Parker, Smith, Turner, and Rowe– han sido hallados en Norteamérica. En este trabajo reportamos el primer registro de un dinosauromorfo no-dinosauriforme del Hemisferio Sur, Dromomeron gigas sp. nov., proveniente de afloramientos norianos de la Formación Quebrada del Barro, al Noroeste de Argentina. El resultado del análisis filogenético recuperó a Dromomeron gigas como parte del grupo monofilético Lagerpetidae, y taxón-hermano de Dromomeron romeri. La inclusión de D. gigas entre los Lagerpetidae sugiere que el tamaño corporal de este linaje también se incrementó a través del tiempo, tal como fue previamente demostrado para Dinosauriformes; y que los lagerpetidos alcanzaron un tamaño mayor del actualmente conocido. El nuevo hallazgo provee novedosa información al conocimiento de la radiación basal de Dinosauromorpha constituyendo el primer registro de una asociación faunística noriana de dinosaurios con dinosauromorfos no-dinosaurios fuera de Norteamérica.